Extent of Resection and Residual Tumor Thresholds for Postoperative Total Seizure Freedom in Epileptic Adult Patients Harboring a Supratentorial Diffuse Low-Grade Glioma. Issue 2 (5th November 2018) - Still, Megan E H; Roux, Alexandre; Huberfeld, Gilles; Bauchet, Luc; Baron, Marie-Hélène; Fontaine, Denys; Blonski, Marie; Mandonnet, Emmanuel; Guillevin, Remy; Guyotat, Jacques; Taillandier, Luc; Capelle, Laurent; et al.
Abstract: BACKGROUND: Epileptic seizures impair quality of life in diffuse low-grade glioma (DLGG) patients. Tumor resection significantly impacts postoperative seizure control, but the precise extent of resection (EOR) required for optimal seizure control is not clear yet. OBJECTIVE: To identify the EOR and residual tumor volume that correlated to postoperative seizure control, defined as a total seizure freedom (Class 1A in reference to Engel classification system) with and without antiepileptic drugs in patients undergoing surgical resection of supratentorial DLGG. METHODS: A retrospective review was conducted of all patients who underwent first-line surgical resection of supratentorial DLGG who presented with preoperative seizures without adjuvant oncological treatment. EOR and residual tumor volume were quantified from pre- and post-operative magnetic resonance imagings. Receiver operating characteristic curves were plotted to determine the EOR and residual tumor volume that corresponded to optimal postoperative seizure control. RESULTS: Of the 346 included patients, 65.5% had controlled seizures postoperatively, with higher age at resection (adjusted OR per unit, 1.03 [95% confidence interval:1.01-1.06], P = .043) and higher percentage of resection (adjusted OR per unit, 1.02 [95% confidence interval:1.00-1.03], P < .001) found as independent predictors of postoperative seizure control. Optimal EOR was ≥91% and optimal residual tumor volume was ≤19 cc to improve postoperative seizure control. CONCLUSION: Postoperative seizure control is more likely when EOR is ≥91% and/or when residual tumor volume is ≤19 cc in supratentorial DLGG gliomas who present with seizures. Resected peritumoral cortex should, however, be taken into account in future studies.